The Ripple Effect of Systemic Stress: Teacher Burnout, School Climate, and Parental Influence on Adolescent Emotional Well-Being - Rani, Rajiv Sandya; Shakthi, Uva Khalkho (Journal of Research in Vocational Education, 2025)
Student’s psychological growth and development in terms of mental, physical and intellectual ability is significantly influenced by teacher burnout, parental stress and school climate. The research report has provided an overview of the major factors and overall effects of the unfavourable environment that hinders students' advancement. In addition to that, the professional strain of teachers placed on students most of the time, moreover, teachers' personal stress-reduction styles also can lead to major emotional burnout, psychological tiredness, and unfavorable interaction patterns among students. Not only parents' mental health are drastically declining due to financial strain, work-life imbalance, and fear over their child's future, but these factors also create a stressful home atmosphere which may affect the psychological growth of students. The aim of the present review is to draw an insight into how teacher burnout, school climate and parental stress affects students’ mental health, especially on emotional burnout.